The Effect of Siputspin Learning Media on Symmetry Material in Grade V Elementary School - Maulani, Maghfiroh Izza; Putri, Ashma Nur Hanifah Heninda; Faddliyah; Afifah, Novia Nur; Pangestu, Aji (Proceeding International Conference on Science and Engineering, 2020)
Mathematics is a subject that is clearly understood. Likewise, mathematical material seems difficult, one of which is about rotary symmetry. This material is difficult because it requires extra understanding, logic and imagination. For this reason, a siputspin learning media was made to facilitate students. This research was appointed because the author wants to know how much influence the media of siputspin learning makes it easier for fifth grade elementary school students to understand the material of rotating symmetry. The author uses an experimental method whose data source is obtained consisting of interviews, observations, questionnaires, and book reviews. The subjects of this study consisted of several fifth grade elementary school students in Yogyakarta. Determination of the subject is done by random sampling. Data collection techniques are done by interviewing and filling in questionnaires with students and direct observation in class. The data of this study were analyzed descriptively quantitative and qualitative. The results showed that the siputspin learning media can make it easier for students to understand rotational symmetry material. Nevertheless, there are still a number of things that need to be improved from the siputspin learning media to be more effectively applied.